Internet pour les assurances - Beaulne, Michel (Assurances)

(untitled) (HEC Montréal, 1996)
In the wake of the transformation that characterizes the insurance industry, these days, Internet appears to be on the mind of everyone, as a manifestation of the changes happening, a threat to some, an opportunity to others. There are many forms of business activities that can take place over the net: electronic mail, bulletin boards, information search, electronic storefront and mall on the World Wide Web, file transfer and EDI, interactive access to remote computers. The author highlights the possible use of these activities by the various players in the insurance arena to reach their prospects and clients, to promote their products and services, as well as to develop new ones adapted to the growing Internet generation. A repertory is provided of the growing Canadian insurance-related players present on the web. Internet finds its place among emerging technologies to help the insurance community redefine itself in a new paradigm of continuous improvement and mass customization. Will Internet disappear as it came, once the fad has passed? Or will it eliminate all other forms of networks presently used in the insurance world? The author compares the Internet phenomenon to the development of the Post through the ages. There emerges a sense that various forms of networks will survive and coexist, some more robust and secure, in the service of business partners, some more "open" and democratic, accessible to everyone, from the small business all the way to the consumer. Leading the way to democratize the electronic commerce is none other than Internet.